Design and Development of an IoT-Based Smart Farming System for Corn Plant Monitoring in Sumbawa - Bayu Pratama; Satria Wijaya; Faiza Irfan (Lembaga Publikasi Ilmiah Nusantara, 2026)
The development of Internet of Things (IoT) technology has provided significant opportunities to improve agricultural efficiency, particularly in corn farming in Sumbawa, which faces challenges related to climate variability and irrigation management. This study aims to design and implement an IoT-based smart farming system capable of monitoring environmental conditions in real-time. The research employs a prototyping approach by integrating soil moisture, temperature, and pH sensors connected to a cloud-based platform. The results indicate that the system improves water usage efficiency by up to 25% and achieves sensor accuracy of approximately 95%. Additionally, the system enables farmers to make data-driven decisions more effectively. Therefore, the implementation of IoT in corn farming in Sumbawa has proven to enhance productivity and resource efficiency.